A necessidade de privacidade na era da informação: desafios à sociedade democrática - Motta, Ismael Moises da (2022)
This dissertation presents research on the need for the right to privacy to maintain democratic balance in society in the face of the technological potential arising from the information age. Technological advances in recent decades have enabled the economic development of a digital business model based on the expropriation of personal data from individuals connected to the world wide web, posing new challenges to the consolidation of the right to privacy and the maintenance of the balance of power in a democratic society, especially in the scenario of political preference formation. In this context, the discipline of personal data protection was born, whose conception comes from the need to functionalize the right to privacy in the virtual technological environment, also called cyberspace, which, in essence, represents a democratic environment, in which everyone can have access to different information, with autonomy and freedom of ideas and expression. However, this work recognizes the harmful potential of this digital space, which is serving as a means of concentrating power, with the development of a pervasive business model for extracting personal data and personalized technological processing, enabling targeted content. The more time dedicated to the internet, the more intense the digitalization of people's lives, resulting in a greater volume of personal data available for collection and processing. The evolution of the right to privacy demonstrates that its scope of protection adapts to social desires and is conditioned by technological development itself. From an individual point of view, people seem to give up this right and are willing to share personal information online, a characteristic of digital networks themselves. From a social point of view, the possibilities that arise from the expropriation of personal data feed the so-called personalization of content of digital services, that is, the technological intermediation of human interaction in this digital environment. This content user intermediation proves to be susceptible to the dominance of technological capital, allowing control over the environment for the formation of public opinion and political preferences, fundamental in a democratic society.